A Critical Analysis of the Use of the Verb ἀναγινώσκω in the Corpus Paulinum A Reappraisal of the Reading Practice in Early Christianity - De Feo, Stefano (2020)
This article focuses on the value of reading in early Christian communities, starting from a critical analysis of the use of the lexical field of ἀναγινώσκω in the Pauline correspondence. Along with this analytical method, this contribution deals with the most important features of the reading practice in antiquity; subsequently, it analyses in detail the occurrences of the verb ἀναγινώσκω in the Corpus Paulinum, drawing particular attention to the incompatibility of the public reading of these Letters and the liturgical reading of the Scriptures. In fact, if one considers the proto-Christian literary phenomenon, it is noteworthy that right from his first Letter (I Thess 5. 27), Paul exhorts his audience to undertake a public reading of it. Indeed, it is Paul’s wish that his Letter reach the whole Thessalonian community through a communal reading. This difference can be documented through the divergent description of these approaches to the text given by Paul himself, attesting both the practice of public reading in the early Christian communities (II Cor 1. 13) and the liturgical memory of the First Testament (II Cor 3. 14-15). This research purposes to show the development and the progressive acquisition of significance of the reading practice in the Pauline communities: the liturgical reading of Paul’s Letters is regarded as the crowning of their interpretation and not as the starting point of their reception. In the light of the canonization process of Paul’s Letters, Eph 3. 4 constitutes, more than Col. 4. 16, an increase in value of the reading practice and, at the same time, it bears witness to the progressive acquisition of the Corpus Paulinum as Holy Scripture. The centrality of the reader for the community arises from I Tim 4. 13, which shows that literacy might be considered as ratio seminalis in the management of the first hierarchical architecture in the Pauline Churches.
Questo articolo si concentra sul valore della lettura nelle prime comunità cristiane, partendo da un’analisi critica dell’impiego dell’area lessicale ἀναγινώσκω nella corrispondenza paolina. Accanto a questo metodo analitico, il presente contributo affronta gli aspetti più importanti della pratica della lettura nell’antichità; successivamente, esso analizza nel dettaglio le occorrenze del verbo ἀναγινώσκω nel Corpus Paulinum, richiamando in particolare l’attenzione sull’incompatibilità della lettura pubblica di queste Lettere e della lettura liturgica delle Scritture. Infatti, se si considera il fenomeno letterario protocristiano, è importante notare che fin dalla sua prima Lettera (I Tess 5,27), Paolo esorta l’uditorio a effettuare una lettura pubblica. Infatti, la volontà di Paolo è che la sua Lettera raggiunga l’intera comunità dei Tessalonicesi attraverso una lettura comunitaria. Questa differenza può essere documentata dalla diversa descrizione di questi approcci al testo data dallo stesso Paolo, il quale testimonia sia la pratica della lettura pubblica nelle prime comunità cristiane (II Cor 1,13) sia la memoria liturgica del Primo Testamento (II Cor 3,14-15). Questa ricerca mira a mostrare lo sviluppo e la progressiva acquisizione di significato della pratica della lettura nelle comunità paoline: la lettura liturgica delle Lettere di Paolo è considerata il coronamento della loro interpretazione e non il punto di partenza della loro ricezione. Alla luce del processo di canonizzazione delle Lettere di Paolo, Ef 3,4 costituisce, più di Col. 4,16, un accrescimento di valore della pratica della lettura e, parallelamente, testimonia la progressiva acquisizione del Corpus Paulinum come Sacra Scrittura. La centralità del lettore per la comunità emerge da I Tim 4,13, a partire dal quale è possibile considerare l’alfabetizzazione come una ratio seminalis nella gestione della prima architettura gerarchica delle Chiese Paoline.